THE EFFECT OF USING BIO-POEM STRATEGY ON STUDENTS’ WRITING ABILITY IN DESCRIPTIVE PARAGRAPH - rizki amelia; firza khaira maulida (Indonesian Journal of Integrated English Language Teaching, 2017)
The aim of this research was to find out whether there was any significant effect of using bio-poem strategy on students’ ability in writing descriptive paragraph at Mts Darul Falah Salo Kampar Regency. This research was Experimental Research. The design was quasi-experimental research. The writer formulated the problems that would be answered by using the quantitative research. The subject of the research was the second year students of MTs Darul Falah Salo Kampar Regency academic year 2016/2017. The object of this research was bio poem strategy and their writing ability on descriptive paragraph. The writer took two classes: experimental and control. Experiment class was with 17 students, and control class was with also 17 students. To analyze the data, the writer adopted independent sample T-test formula by using SPSS 20 version. After analyzing the data, the writer found that the students’ writing ability was taught by using bio-poem strategy at MTs Darul Falah Salo was categorized into good level. The students’ writing ability was taught without using bio-poem strategy at MTs Darul Falah Salo was categorized into less level. Writer found that Ha: sig. (2 tailed)<0.05. From the research finding it can be concluded that teaching writing by using bio-poem strategy gave large effect on students’ writing ability in descriptive paragraph at MTs Darul Falah Salo Kampar Regency.